Implementing modular integrated construction in high-rise high-density cities: perspectives in Hong Kong. Issue 3 (3rd April 2023) - Pan, Wei; Yang, Yi; Pan, Mi
ABSTRACT: Modular construction has been widely promoted with numerous benefits, but the promotion has largely been for low- to medium-rise buildings. The implementation of high-rise modular buildings in high-density cities remains limited. This paper aims to investigate modular adoption in high-rise high-density cities by examining drivers, constraints and strategies with the case of modular integrated construction in Hong Kong. The research was carried out through a literature review, expert interviews and a questionnaire survey with key stakeholders. The most important drivers were identified to be faster construction and shortened project duration, financial incentives, better quality control, policy initiative and promotion and improved workers' well-being. The most significant constraints were found to be over-stringent regulations, limited codes and standards, limited capable suppliers and contractors, logistics challenges and loss of saleable areas. The most important success strategies were identified relating to financial incentives, standards and codes, technical solutions, transport regulations and prioritized adoption in public housing. A systems framework is proposed to address the complexity of modular adoption within social, technological, economic, supply chain and regulatory contexts. The findings should help accelerate the adoption of modular methods in high-rise high-density cities and contribute a systematic approach to informing future research into modular construction.